2008
DOI: 10.1002/nbm.1216
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer imaging of 9L gliosarcoma and human glioblastoma xenografts

Abstract: Amide proton transfer (APT) imaging is a variant of magnetization transfer (MT) imaging, in which the contrast is determined by a change in water intensity due to chemical exchange with saturated amide protons of endogenous mobile proteins and peptides. In this study, eight Fisher 344 rats implanted with 9L gliosarcoma cells and six nude rats implanted with human glioblastoma cells were imaged at 4.7 T. There were increased signal intensities in tumors in the APT-weighted images. The contrast of APT imaging be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
100
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 44 publications
11
100
2
Order By: Relevance
“…Normal, healthy brain tissue displayed negative and lower APT values compared with tumor at baseline and 1 wk ( Fig. 2A, white arrow) as reported in previous literature (16). In all untreated control animals, the enhanced area increased drastically at 1 wk relative to baseline (7. ; P = 0.87).…”
Section: Comparison Between With and Without Treatment In A Gbm Linesupporting
confidence: 79%
See 1 more Smart Citation
“…Normal, healthy brain tissue displayed negative and lower APT values compared with tumor at baseline and 1 wk ( Fig. 2A, white arrow) as reported in previous literature (16). In all untreated control animals, the enhanced area increased drastically at 1 wk relative to baseline (7. ; P = 0.87).…”
Section: Comparison Between With and Without Treatment In A Gbm Linesupporting
confidence: 79%
“…The images obtained at 29 frequency offsets were first collected to obtain a z-spectrum. The z-spectrum was fitted on a pixel-by-pixel basis according to the procedure using the 12th-order polynomial fitting on positive and negative sides of frequency offsets, respectively, as previously reported (16,17). Subsequently, the original z-spectrum was corrected pixel-wise for the any B 0 inhomogeneity through interpolation and centering of the z-spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…The high APT signal in tumours can be attributed to abundant concentration of mobile proteins and peptides in cellular cytoplasm. Higher cell density reported in HGGs in a human study [22] and animal study [23] would be a cause of higher concentration of mobile proteins and peptides. The present results revealed that the ADC did not differ between the high and low grades, indicating that the cell density was not very different between the grades whereas the APT signals were clearly different between the grades.…”
Section: Discussionmentioning
confidence: 92%
“…Chemical exchange was first investigated by nuclear magnetic resonance (NMR) (1)(2)(3)(4) and was proposed as an MRI method by Wolff and Balaban (5); however, it was only recently introduced as a clinical technique (6). Its utility as a contrast mechanism has been demonstrated in brain tumors (7,8) and in identification of reperfusable regions of stroke damage (9). As the chemical exchange is sensitive to hydrogen ion concentration, CEST experiments may allow quantification of pH as well.…”
Section: Introductionmentioning
confidence: 99%